2007
DOI: 10.1007/s11515-007-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habitats of blue sheep (Pseudois nayaur) during winter and spring in Helan Mountains, China

Abstract: The feeding habitat selection of blue sheep (Pseudois nayaur) was studied by direct observation method in the Helan Mountains, China during winter (from Novembe r to December) and spring (from April to June) from 2003 to 2004. We established 25 line transects to collect information on feeding habitats used by blue sheep. Blue sheep in the study area preferred mountain savanna forests, a habitat dominated by Ulmus glaucescens, with medium tree density (<4 individuals / 400 m 2 ), moderate tree height (4-6 m), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…Pseudois nayaur show a similarly narrow feeding breadth across its range, e.g., in Ninxia Hui Autonomous Region, Inner Mongolia (Liu et al 2007a (Harris and Miller 1995, Miller and Schaller 1998, Schaller 1998, Mishra et al 2004, Shrestha et al 2005, Liu et al 2007a, Suryawanshi et al 2009 ). This shift is particularly pronounced in winter when graminoid resources become limited or where competition with domestic livestock or other wild ungulates occurs (Mishra et al 2004, Liu et al 2007a, Suryawanshi et al 2009 ). Ultimately, the local plant composition determines the availability; for example, a complete lack of woody species in some areas totally precludes that component from entering the diet Miller 1995 , Miller andSchaller 1998 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pseudois nayaur show a similarly narrow feeding breadth across its range, e.g., in Ninxia Hui Autonomous Region, Inner Mongolia (Liu et al 2007a (Harris and Miller 1995, Miller and Schaller 1998, Schaller 1998, Mishra et al 2004, Shrestha et al 2005, Liu et al 2007a, Suryawanshi et al 2009 ). This shift is particularly pronounced in winter when graminoid resources become limited or where competition with domestic livestock or other wild ungulates occurs (Mishra et al 2004, Liu et al 2007a, Suryawanshi et al 2009 ). Ultimately, the local plant composition determines the availability; for example, a complete lack of woody species in some areas totally precludes that component from entering the diet Miller 1995 , Miller andSchaller 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2000) and Wu et al (1990) each observed the dwarf blue sheep to have mixed diets, though specific proportions of the foraging classes were not given. Many specialist herbivores show considerable temporal variation in the contribution of foraging classes to their diets in response to environmental factors (Bodmer 1990, Brown and Doucet 1991, Liu et al 2007a. Pseudois nayaur is, in its natural habitat, predominantly a grazer, preferring graminoids, though shifts its diet along the grazer-browser continuum as a result of seasonal availability, competitive exclusion by sympatric grazers, and local plant com position dwarf blue sheep fed unevenly on the most common species (Pearson's χ 2 = 90.996, df = 16, p < 0.001).…”
Section: Food Niche Overlapmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternately, smaller herds could possibly be more common in winter when forage is poor (Liu et al 2007).…”
Section: Variability Of Estimates Across Seasonsmentioning
confidence: 99%